Revolutionizing Cattle Breeding: Studies on In-vitro Embryo Production in Sahiwal Cows with Sexed Semen - Farheen, S. R.; Arunakumari, G.; Reddy, K. R. C.; Reddy, K. C. S.; Nagaraj, P.; Priyanka, B. (International Journal of Bio-resource and Stress Management, 2024)
The experiment was conducted during 2023 (January–October), at Embryo transfer and in-vitro fertilization project, Department of Veterinary Gynaecology and Obstetrics, College of Veterinary Science, Korutla, Jagitial district, Telangana, India. The objective of the present study was to evaluate the effect of Follicle Stimulating Hormone stimulation on In-Vitro Fertilization rates with sexed semen in-vitro matured oocytes collected from Sahiwal cows via Ovum Pick-Up procedure. Irrespective of the estrus cycle, 20 non-lactating cows were divided into two equal groups. Animals in group 1 (non-stimulated, n=10) were subjected to ovum pick-up once at the random stage of the estrous cycle. Animals in group 2 (FSH Stimulated, n=10) were put under CIDR+FSH super stimulation protocol and subjected to OPU after 36 hours of coasting period. Viable oocytes were in-vitro fertilized using sexed-sorted semen after 24 hours of In-vitro maturation. Follicle stimulating hormone stimulation increased the secondary polar body extrusion rate (non-stimulated, 69.10±2.00% vs FSH stimulated, 79.84±1.55%), cleavage rate on day 1(non-stimulated, 60.69±3.04% vs FSH stimulated, 69.10±2.26%), cleavage rate on day 3 (non-stimulated, 35.62±3.32 vs FSH stimulated, 43.59±1.90), mean number of In-vitro produced blastocysts animal-1 (non-stimulated, 1.50±0.16 vs. FSH-treated, 4.10±0.23%) and blastocyst conversion rate (non-stimulated, 23.98±2.39% vs FSH-treated, 34.35±3.42%). We concluded that FSH stimulation was effective in improving In-vitro oocyte competence for embryo production in non-lactating Sahiwal cows with sexed semen.